ANALISIS PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2017-2019 - Lestari, Novera Ayu; Mahfud, Mohammad Kholiq (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This research was conducted with the aim of analyzing the relationship between working capital management and company profitability. Working capital management is an effort to manage working capital that is used to support the company's operations. The components of working capital management (cash conversion cycle, accounts receivable collection period, inventory conversion period, and debt deferral period) were analyzed collectively on profitability. The population in this study were all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019, totaling 30 companies. The number of samples taken was 16 companies. The sample was taken using purposive sampling method and as many as 14 companies were eliminated because outliers had been made. The method used in this study is multiple regression analysis using the SPSS 20.0 bandu device. The results of this study indicate that the cash conversion cycle, debt collection period, and inventory conversion period have a negative and significant effect on company profitability. However, the debt suspension period has a positive and significant impact on the company's profitability